Internalisasi Nilai-Nilai Kepemimpinan Islam dalam Organisasi Santri Pesantren (Penelitian di Pesantren Ibnu Siena Mulia Cikoneng Kabupaten Ciamis) - Ridwan, Muhammad Arif; Hasanudin, Hasanudin; Masturoh, Imas (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2020)
This study aims: (1) To find out how to plan the internalization of leadership values ​​through the Islamic Boarding School Ibnu Siena Mulia (OSPIS) santri organization. (2) To find out how the implementation of the internalization of leadership values ​​through the Islamic boarding school santri Ibnu Siena Mulia organization. (3) To find out how the results of the internalization of leadership values ​​through the Pesantren Ibnu Siena Mulia santri organization. This research is a qualitative field research. Data collection was carried out by using interview, observation and documentation techniques. The data analysis technique used is descriptive analysis. The results of this study indicate that: 1) Planning the internalization of leadership values ​​in the OSPIS Ibnu Siena Mulia Islamic Boarding School is carried out in 4 steps. The first step is the formation of the committee, the second step is the reporting of the old OSPIS committee, the third step is the election of the new OSPIS chairman, and the fourth step is the formation of the new OSPIS structure. 2) The internalization of leadership values ​​in the Ibnu Siena Mulia Islamic Boarding School OSPIS is carried out through the division of divisions with their respective main duties and functions. The internalization of leadership values ​​is carried out in five forms, namely lectures, education, uswah hasanah, training and the environment. 3) Internalization of leadership values ​​in the Ibnu Siena Mulia Islamic Boarding School OSPIS can be felt by the board and boarding school with the formation of an attitude of trust, responsibility, social spirit and good role models.